2012
DOI: 10.1097/01.pra.0000415080.51368.cf
|View full text |Cite
|
Sign up to set email alerts
|

Inevitable Suicide

Abstract: The author suggests that a new paradigm may be needed which holds that some suicides may be inevitable. The goal of this paradigm would be to diminish the sense of failure and inadequacy felt by many psychiatrists who experience the suicide of a patient and to increase understanding of the unique biopsychosocial profile of those whose suicides appear to be inevitable. The author stresses that this proposed paradigm should not be misconstrued as therapeutic nihilism but rather should serve to stimulate efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…The VZ was considered to be unachievable also because of limitations of contemporary psychiatry: current clinical methods are not effective enough to save every person at risk of suicide. This, too, is consistent with the existing literature [ 33 ]. A related concern was that the VZ will contribute to the general public underestimating the severity of psychiatric illnesses or overestimating the ability of healthcare to treat these illnesses.…”
Section: Discussionsupporting
confidence: 93%
“…The VZ was considered to be unachievable also because of limitations of contemporary psychiatry: current clinical methods are not effective enough to save every person at risk of suicide. This, too, is consistent with the existing literature [ 33 ]. A related concern was that the VZ will contribute to the general public underestimating the severity of psychiatric illnesses or overestimating the ability of healthcare to treat these illnesses.…”
Section: Discussionsupporting
confidence: 93%
“…Both unipolar depression and bipolar disorder present clinically severe conditions characterized by recurring episodes of depressive symptom categories, and in the latter periods of mania, with a life-long lasting prevalence [29-31]. It has been suggested that whereas mood refers to the underlying or longitudinal emotional state, affect pertains to the external/visible expression of the individual observed by others [32]. Unipolar depression and bipolar disorder, of the depressive disorder spectrum of mood disorders, present severe illnesses and are leading causes of disability and suffering among a large population of afflicted individuals [33].…”
Section: Mood Disorders Genes Pathophysiology and Environmentmentioning
confidence: 99%
“…Mood disorder, also known as mood affective disorder, is a group of conditions characterized by disturbance in a person's mood, ranging from elevated (mania or hypomania) to depressed moods (major depression). [1] In fact, mood disturbances may also oscillate between mania and depression, such as in bipolar disorder. [2] Other subtypes include dysthymia (milder form of major depression), cyclothymiacs (milder form of bipolar disorder) and adjustment disorder (abnormal reaction to a life stressor).…”
Section: Introductionmentioning
confidence: 99%